ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU PETANI DI DESA MUARA LANGKAP KECAMATAN BERMANI ILIR DALAM MENGHADAPI PENURUNAN HARGA LADA HITAM - Akbar, Muhammad; Fariadi, Herri; Sumartono, Eko (University of Prof. Dr. Hazairin, SH, 2024)
The results of a survey by researchers on the price of black pepper in Muara Langkap Village, Bermani Ilir District, Kepahiang Regency, currently (2023) is around IDR 45,000 lower than the previous year (2022) which was around IDR 49,0000. The low price of black pepper has caused losses for farmers. Farmers whose only source of income is pepper still sell all the pepper they have. This research is a qualitative research. The data obtained were analyzed using in-depth data processing methods from observations, interviews, and literature. The results of the study concluded that the average assessment of farmer knowledge was 2.62, which means that farmers agree that the price of black pepper is currently decreasing. Farmer behavior towards the decline in the price of black pepper averaged 26.45, including the high category, which means that farmers prefer to sell black pepper directly. The factors that influence farmers' behavior towards the decline in black pepper prices are knowledge (X1), attitude (X2) and training (X5), while the action factor (X3), facilities (X4) and regulations/policies (X6) do not affect. All factors together have a significant influence, because the significant value of 0.000 is smaller than 0.05.